Investigation of cytotoxicity of negative control peptides versus bioactive peptides on skin cancer and normal cells: a comparative study. (August 2012) - Almansour, Nahlah M; Pirogova, Elena; Coloe, Peter J; Cosic, Irena; Istivan, Taghrid S
Background: Resonant recognition model-myxoma virus (RRM-MV), a bioactive peptide analogue for myxoma virus MV-T5 protein, was computationally designed by the RRM. In this study, the anticancer effects of RRM-MV were assessed in vitro against four negative control peptides on human skin cancer and normal cells.Results & discussion: The effects of RRM-MV versus negative control peptides on cells were evaluated by quantitative and qualitative assays. The RRM-MV treatment was able to induce cell death in cancer cells without triggering similar effects on normal cells. However, the negative control peptides produced no toxic effects on skin cancer and normal cells. No effects on human erythrocytes were detected when treated with all peptides.Conclusion: It is suggested that the RRM can be applied to design therapeutic anticancer peptides.